Association between baseline pro-inflammatory cytokines and brain activation during social exclusion in patients with vulnerability to suicide and depressive disorder. (January 2019) - Conejero, I; Jaussent, I.; Cazals, A.; Thouvenot, E.; Mura, T.; Le Bars, E.; Guillaume, S.; Squalli, S.; Courtet, P.; Olié, E.
Highlights: Baseline blood IL-1 decreases orbitofrontal activation in response to social exclusion. Baseline blood IL-2 increases neural activation in response to social exclusion. No influence of suicidal status on the immune-brain relationship underlying social exclusion. Abstract: Background: Neuroimaging studies suggest that social distress and suicidal vulnerability share common cerebral bases. Moreover, increased peripheral inflammatory activity is involved in both social distress and suicidal behavior. Objective: To evaluate, in suicidal and non-suicidal individuals, the association between the activation of specific cerebral regions (anterior cingulate, insula and orbitofrontal cortex) during experimental social exclusion and the baseline blood levels of the pro-inflammatory cytokines interleukin-6 (IL-6), interleukin-1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α) and of the anti-inflammatory cytokine interleukin-2 (IL-2). Methods: In total, 101 euthymic women were recruited: 42 suicide attempters (SA), 40 affective controls (AC), and 19 healthy controls (HC). During functional MRI (fMRI), they performed the Cyberball game, a validated social exclusion task. Blood levels of IL-1β, IL-6, TNF-α and IL-2 were measured prior to fMRI. The activation of insula, orbitofrontal cortex (OFC) and anterior cingulate cortex (ACC) during the explicit social exclusion (ESE) vs social inclusion (INC) conditions of the Cyberball game was analyzed in function of the baseline cytokine levels. Results: IL-1β was negatively associated with right OFC activation (p = 0.01) in ESE vs. INC, whereas IL-2 was positively associated with activation of the right ACC (p = 0.02), insula (p = 0.002) and OFC (p = 0.004) in ESE vs. INC. These associations remained significant after controlling for group, indicating that they were independent of the suicidal status. Conclusion: Baseline IL-1β and IL-2 blood levels are differentially associated with cerebral activation involved in the perception of social exclusion, independently of suicidal behavior. Our results may help to better understand the role of basal inflammation in social distress and its link with mood disorder pathophysiology.